EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN JAGUNG (Zea mays.L) DI KECAMATAN BUALEMO KABUPATEN BANGGAI - Rinawati; Yatim, Hertasning; Yatim, Herwin; Djamaluddin, Ismail (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
This study aims to analyze the suitability of land for corn plants and to determine the improvement efforts and potential land suitability of corn plants in Bualemo District. This research was carried out from August 2022 to February 2023 in Nipakalemoan, Sampaka and Bualemo A Villages, Bualemo District. The method used is a descriptive method that is used to analyze several results using a matching approach. The results of the research obtained are the suitability of corn crop land in Bualemo sub-district actually, namely at points 1,2,3, namely S3 (marginal) while the limiting factors are wet saturation, N-Total, P2O5 and K2O. Furthermore, for improvement efforts by carrying out liming and adding organic matter, as well as applying fertilizer to corn fields with medium to high soil management levels. Direction of corn improvement efforts in Bualemo District obtained the suitability of potential land for corn plants at points 1,2 and 3, in Bualemo District, namely the S1 criterion (very suitable).